The Oxford handbook of deliberative democracy - Bächtiger, André 1971-; Dryzek, John S. 1953-; Mansbridge, Jane J. 1939-; Warren, Mark ca. 20./21. Jh (Oxford University Press, 2018)
Deliberative democracy has been the main game in contemporary political theory for two decades and has grown enormously in size and importance in political science and many other disciplines, and in political practice. The Oxford Handbook of Deliberative Democracy takes stock of deliberative democracy as a research field, as well as exploring and creating links with multiple disciplines and policy practice around the globe. It provides a concise history of deliberative ideals in political thought while also discussing their philosophical origins. It locates deliberation in a political system with different spaces, publics, and venues, including parliament and courts but also governance networks, protests, mini-publics, old and new media, and everyday talk. It documents the intersections of deliberative ideals with contemporary political theory
Keywords: Deliberative democracy; Deliberative Demokratie; Aufsatzsammlung